2013
DOI: 10.1055/s-0033-1358730
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Parameters and Adipokine Profile in Growth Hormone Deficient (GHD) Children Before and After 12-Month GH Treatment

Abstract: It is a common knowledge that GH exhibits a large number of metabolic effects, involving lipid and glucose homeostasis. The aim of the study was to investigate the effect of one year GH therapy on metabolic parameters and adipokines in GH deficient (GHD) children. Sixteen prepubertal children (11 M and 5 F) with complete GHD (age range: 3.4-14.7 years) and 20 (13 M and 7 F) age and sex-matched healthy children (age range: 4.6-12.3 years) were studied. Blood was collected from patients before starting GH therap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
42
1
6

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(53 citation statements)
references
References 15 publications
4
42
1
6
Order By: Relevance
“…Our data are in agreement with some studies that have documented that GH treatment does not seem able to strongly modify resistin levels in GHD adults [10,20], although we found a trend to an increase in resistin levels after 12 months, though not statistically significant. Partially in line with our results, Nozue et al [21] demonstrated a rise in resistin after short-term GH therapy in GHD children, while López-Siguero et al [12] showed a decline in resistin at 6 months of GH treatment and these data are in line with those of Meazza et al [19] who showed a decrease in resistin levels. However, despite the lack of a statistically significant change, the trend to an increase in resistin in our patients during GH treatment is concomitant with a significant reduction in insulin sensitivity, as demonstrated by the decline in QUICKI and ISI Matsuda, in line with previous studies.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our data are in agreement with some studies that have documented that GH treatment does not seem able to strongly modify resistin levels in GHD adults [10,20], although we found a trend to an increase in resistin levels after 12 months, though not statistically significant. Partially in line with our results, Nozue et al [21] demonstrated a rise in resistin after short-term GH therapy in GHD children, while López-Siguero et al [12] showed a decline in resistin at 6 months of GH treatment and these data are in line with those of Meazza et al [19] who showed a decrease in resistin levels. However, despite the lack of a statistically significant change, the trend to an increase in resistin in our patients during GH treatment is concomitant with a significant reduction in insulin sensitivity, as demonstrated by the decline in QUICKI and ISI Matsuda, in line with previous studies.…”
Section: Discussionsupporting
confidence: 92%
“…Indeed, a possible mediator of the GH-modulated insulin sensitivity may be resistin, which has been shown to be linked to obesity and insulin resistance [18]. Higher resistin levels in untreated GHD children than controls have already been documented [19], while the effect of GH treatment is controversial. Our data are in agreement with some studies that have documented that GH treatment does not seem able to strongly modify resistin levels in GHD adults [10,20], although we found a trend to an increase in resistin levels after 12 months, though not statistically significant.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have reported a decrease in leptin levels in short children with [45,46] and without [42] GH deficiency after 1 year of GH therapy. Conversely, Meazza et al [47] have detected a significant increase in leptin levels after 1 year of GH treatment in children with GH deficiency.…”
Section: Discussionmentioning
confidence: 98%
“…Importantly, it results in an overall reduction of fat mass, including a shift in adipocyte volume and size toward normal [78, 79]. Levels of insulin and adipokines are partly normalized, and especially in adult GHD, lipid metabolism is improved [39, 80]. Patients with LS show clinical manifestations that are similar, although not identical, to GHD.…”
Section: What Does This Mean For the Clinical Use Of Treatments That mentioning
confidence: 99%